2021
DOI: 10.12681/bgsg.27155
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating deformation seismicity patterns before the March 3, 2021 Thessaly strong earthquake. First results

Abstract: A widely felt strong shallow earthquake with Mw 6.3 magnitude occurred in Thessaly (Central Greece) on March 3, 2021. This recent strong event attracted our interest to apply and evaluate the capabilities of the Accelerating Deformation method. Based on the recently proposed generalized Benioff strain idea which could be justified by the terms of Non-Extensive Statistical Physics (NESP), the common critical exponent was calculated in order to define the critical stage before a strong event. The present analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…The results demonstrated that regional seismicity approached criticality a few days before the M w 6.3 earthquake that occurred on 3 March 2021 in the Thessaly region, in agreement with the results in [57]. In other words, the curve of the power spectrum, Π(φ), in the natural time domain that characterizes the evolution of the regional seismicity, coincided with the theoretical curve of critical point phenomena a few days before the M w 6.3 mainshock, in a similar way to that of non-equilibrium critical systems.…”
Section: Discussionsupporting
confidence: 90%
“…The results demonstrated that regional seismicity approached criticality a few days before the M w 6.3 earthquake that occurred on 3 March 2021 in the Thessaly region, in agreement with the results in [57]. In other words, the curve of the power spectrum, Π(φ), in the natural time domain that characterizes the evolution of the regional seismicity, coincided with the theoretical curve of critical point phenomena a few days before the M w 6.3 mainshock, in a similar way to that of non-equilibrium critical systems.…”
Section: Discussionsupporting
confidence: 90%
“…were observed [Valkaniotis et al 2021;Papathanassiou et al, 2022], the earthquakes have been attributed to a blind fault [Chatzipetros et al, 2021;Pavlides and Sboras, 2021]. The wealth of data sparked new interest in the area, with several aspects of the sequence having been studied, such as accelerating deformation seismicity patterns [Chatzopoulos, 2021] and earthquake early warning [Spingos et al, 2021].…”
Section: George Kavirismentioning
confidence: 99%
“…Strong arguments suggest that the earthquake generation process can be considered as a critical point phenomenon that culminates with a large event, which is the critical point [14][15][16][17][18][19][20][21][22][23][24]. New findings regarding the complex dynamics that characterize various geodynamic phenomena illustrate stimulating features in the framework of new concepts, such as that of non-extensive statistical physics [17][18][19][20][21][22][23][24], multiresolution wavelets analysis [25][26][27] and of the novel time domain, termed as natural time [22,23,[28][29][30][31][32][33][34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%